Laryngeal mask versus intubation for adenoidectomies in children: Analysis of 1, 500 operations. (10th January 2019) - Gehrke, Thomas; Hackenberg, Stephan; Steinhübel, Bernhard; Hagen, Rudolf; Scherzad, Agmal
Abstract : Objectives/Hypothesis: To evaluate whether endotracheal intubations are superior to the use of laryngeal masks in the airway management for adenoidectomies in pediatric patients in terms of safety and duration of surgery. Study Design: Retrospective case series. Methods: A retrospective analysis of 1, 500 adenoidectomies in children using laryngeal mask or endotracheal intubation for intraoperative ventilation between 2009 and 2017. Data collected included complications, duration of surgery, and duration of induction and emergence from anesthesia. Results: The use of laryngeal masks did not accelerate the time needed for induction and emergence of anesthesia although significantly increasing the duration of surgery itself. There also were significantly more complications during and after anesthesia when using a laryngeal mask. In 10% of the children, the laryngeal mask had to be replaced by an endotracheal tube intraoperatively. Conclusions: There is no reason to recommend the use of a laryngeal mask as the first choice of airway management regarding adenoidectomies in children. Level of Evidence: 3 Laryngoscope, 129:E383–E388, 2019